Świadomość stanów emocjonalnych a osiągnięcia w nauce szkolnej uczniów słabowidzących w okresie wczesnej adolescencji - Kucharczyk, Izabella (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2018)
The purpose of this article is to present the results of research of the relationships between awareness of one’s emotions and the educational achievements of students with visual impairments during early adolescence. The study included 60 pupils from secondary schools in the region of Masovia. The study used the Emotion Awareness Questionnaire – Revised EAS-30-R. Rieffe, P. Oosterveld, A.C. Miers, M.M. Terwogt (2008) in the Polish adaptation by I. Kucharczyk and A. Dłużniewska, as well as school grades.